2000
DOI: 10.1074/jbc.275.19.14242
|View full text |Cite
|
Sign up to set email alerts
|

Ornithine Decarboxylase of Stagonospora (Septoria) nodorum Is Required for Virulence toward Wheat

Abstract: A knockout strain of Stagonospora (Septoria) nodorum lacking the single ornithine decarboxylase (ODC) allele has been created by targeted gene replacement. A central region of the S. nodorum ODC gene was isolated by polymerase chain reaction using degenerate oligonucleotides and used to probe a genomic library. The gene was sequenced and the encoded ODC protein sequence was shown to be similar to those from other fungi. The functionality of the S. nodorum ODC was confirmed by complementation of an Aspergillus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 35 publications
1
35
0
Order By: Relevance
“…These include four genes encoding acid protease A (eapC), cross-pathway control protein 1 (CPC1), mitogene-activated protein kinase (Cpmk1), and G-protein CPGB1 identified previously in C. parasitica (Choi et al, 1995(Choi et al, , 2005Jara et al, 1996;Kasahara and Nuss, 1997;Park et al, 2004;Wang et al, 1998), and 13 genes with high degree of similarity with genes found in Sordariomycetes phytopathogens F. graminearum (Guldener et al, 2006) and M. grisea (Dean et al, 2005). Among the newly identified genes were homologues of ODC1, encoding ornithine decarboxylase, that is necessary for wheat infection by the wheat pathogen Stagonospora nodorum (Bailey et al, 2000) and FOW1, encoding a mitochondrial carrier protein, which is required specifically for colonization in the plant tissue by F. oxysporum (Inoue et al, 2002). C. parasitica EST cluster CLS2961 encodes a homologue of cyclophilin that has been shown to act as a virulence determinant and to be associate with penetration peg formation and appressorium turgor generation in M. grisea (Viaud et al, 2002).…”
Section: Pathogenecity Related Genes In C Parasiticamentioning
confidence: 95%
“…These include four genes encoding acid protease A (eapC), cross-pathway control protein 1 (CPC1), mitogene-activated protein kinase (Cpmk1), and G-protein CPGB1 identified previously in C. parasitica (Choi et al, 1995(Choi et al, , 2005Jara et al, 1996;Kasahara and Nuss, 1997;Park et al, 2004;Wang et al, 1998), and 13 genes with high degree of similarity with genes found in Sordariomycetes phytopathogens F. graminearum (Guldener et al, 2006) and M. grisea (Dean et al, 2005). Among the newly identified genes were homologues of ODC1, encoding ornithine decarboxylase, that is necessary for wheat infection by the wheat pathogen Stagonospora nodorum (Bailey et al, 2000) and FOW1, encoding a mitochondrial carrier protein, which is required specifically for colonization in the plant tissue by F. oxysporum (Inoue et al, 2002). C. parasitica EST cluster CLS2961 encodes a homologue of cyclophilin that has been shown to act as a virulence determinant and to be associate with penetration peg formation and appressorium turgor generation in M. grisea (Viaud et al, 2002).…”
Section: Pathogenecity Related Genes In C Parasiticamentioning
confidence: 95%
“…In plants, odc expression is induced by 2,4-D, GA 3 and by pollination (Alabadi et al 1998). It is also interesting to note that Bailey et al (2000) have demonstrated a requirement for ODC in the development of fungal disease in cereals. A knockout strain of Stagonospora nodorum was created by targeted gene replacement.…”
Section: Introductionmentioning
confidence: 99%
“…A knockout strain of Stagonospora nodorum was created by targeted gene replacement. Studies on the pathogenicity of these mutants showed that they were greatly reduced in virulence towards wheat as compared with wild-type strains (Bailey et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Several genes involved in P. nodorum pathogenicity and sporulation, such as those encoding malate synthase, ornithine decarboxylase, mitogen-activated protein kinase, Gα protein subunit, δ-amino laevulinic acid synthase, and mannitol 1-phosphate dehydrogenase have been identified (Bailey et al 2000;Solomon et al 2006Solomon et al 2004aSolomon et al , b, 2005a. A draft genome sequence of P. nodorum strain SN15 comprising 37.2 mega base pairs (Mbp) of nuclear DNA in 107 scaffolds and containing an estimated minimum of 10,762 genes was reported (Hane et al 2007).…”
mentioning
confidence: 98%